Kuat Tekan Mortar OPC Abu Sekam Padi Pada Suhu Tinggi - Mirza Afrian; Monita Olivia; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research examines the partial replacement of cement mortar with the OPC by rice husk ash as a binding material. Rice husk Ash (RHA) has used silica content of 90%. Compressive strength was tests are carried out on the basis of the percentage of rice husk ash and its time variations of the treatment. Variation of rice husk ash used is 10%, 15%, and 20%. Samples was curing in water for 28 days before furnace with variations of temperature 250°C, 500°C, and 750°C for 3 hours. This research showed that a mixture of mortar with the replacement of the 15% rice husk ash cement against the OPC provides optimum results against compressive strength value, not only on the maintenance of room temperature but also at 250°C and 500°C. Compressive strength of all types of cement has increased at temperature of 250. The higher the replacement of cement by rice husk ash will weaken the compressive strength of mortar, but spalling and cracking doesn't happen on every OPC cement replacement by RHA.Keywords: Cracking, high temperature, OPC, rice husk ash, spalling,